Meningkatkan Kemampuan Mengajar bagi Calon Guru Sekolah Dasar - Hidayah, Yayuk; Widodo, Bali; Ulfah, Risti Aulia (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
This study aims to determine the field observation activities of PPKn SD learning in improving the teaching ability of Pkn to prospective elementary school teacher students at Ahmad Dahlan University Yogyakarta in the 2019/2020 academic year. The method used in this research is descriptive qualitative. The data collection instruments were lecturers' diaries, observation sheets, interview guides and reflection sheets. The research was carried out in the Ahmad Dahlan University Primary School Teacher Education (PGSD) study program in the Elementary School PPKn Learning course for the 2019/2020 academic year. The results showed that efforts to improve Civics teaching skills for elementary school teacher candidates were carried out in three ways, namely: 1) Internalizing Civics pedagogical skills in Elementary Schools through innovative elementary school civics education practice development courses, 2) habituation of elementary school civics pedagogic skills and 3 ) the existence of supporting activities, namely through the Field Observation of PPKn Learning in Elementary Schools to support the pedagogic skills of PKn Elementary School Students of Elementary School Teacher Education (PGSD).